ANALISIS KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN DENGAN RISIKO SEBAGAI VARIABEL MEDIASI - Siwi Khasanah; Sri Hermuningsih; Gendro Wiyono (FE Program Studi Manajemen, 2020)
This research is proposed to find the impact of decisive investment, decisive funding, Policy of Dividend on the value of the company and the risk as meditation variable at manufacturing companies in property and real estate sectors that were registered in Indonesian stock market. This research used explanatory with quantitative approach. The population of company in this research is manufacturing and and real estate company sectors that were registered in Indonesian stock market in 2012-2018. The techniques which is used for taking samples is using purposive sampling. The analysis technique data uses multiple linear regression, path analysis, and sobel test.Keywords : decisive investment (PER), decisive funding (DER, the policy of dividends (DPR), the value of the company (PBV) and the risk (β).